CONGRESS OF EUROPEAN SOCIETY OF CARDIOLOGY IN PARIS: WHAT PRACTICAL PHYSICIAN SHOULD TAKE FOR THE NOTES - S. Yu. Martsevich (Рациональная фармакотерапия в кардиологии)
The main events of the Congress of the European Society of Cardiology (ESC) held in Paris, (August 27-31, 2011) are highlighted. The results of recently completed randomized controlled studies, pharmacoepidemiological studies, additional analysis of a number of previously completed studies, new clinical ESC guidelines, as well as results of debates on controversial issues in cardiology , assessment of clinical trials data and therapy compliance are presented.